Biophysical Characterization of the Type III Secretion System Translocator Proteins and the Translocator Proteins Attached to Bacterium‐Like Particles. Issue 12 (30th September 2015) - Chen, Xiaotong; Choudhari, Shyamal P.; Kumar, Prashant; Toth, Ronald T.; Kim, Jae Hyun; Van Roosmalen, Maarten L.; Leenhouts, Kees; Middaugh, C. Russell; Picking, Wendy L.; Picking, William D.
Abstract : Diarrhea caused by Shigella, Salmonella, and Yersinia is an important public health problem, but development of safe and effective vaccines against such diseases is challenging. A new antigen delivery platform called bacterium‐like particles (BLPs) was explored as a means for delivering protective antigens from the type III secretion systems (T3SS) of these pathogens. BLPs are peptidoglycan skeletons derived from Lactococcus lactis that are safe for newborns and can carry multiple antigens. Hydrophobic T3SS translocator proteins were fused to a peptidoglycan anchor (PA) for BLP attachment. The proteins and protein–BLP complexes associated with BLPs were characterized and the resulting data used to create three‐index empirical phase diagrams (EPDs). On the basis of these EPDs, IpaB (S higella ) and SipB ( Salmonella ) behave distinctly from YopB ( Yersinia ) under different environmental stresses. Adding the PA domain appears to enhance the stability of both the PA and translocator proteins, which was confirmed using differential scanning calorimetry, and although the particles dominated the spectroscopic signals in the protein‐loaded BLPs, structural changes in the proteins were still detected. The protein–BLPs were most stable near neutral pH, but these proteins' hydrophobicity made them sensitive to environmental stresses. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4065–4073, 2015